THE LEVEL OF DEPRESSION AND ANXIETY IN STUDENTS, LEARNING IN MEDICAL UNIVERSITY OF UKRAINE - I. V. Gusakova; O. D. Omelchenko; O. A. Nikolaenko; O. V. Bogomaz (Juvenis Scientia, 2017)
The article analyzes the results of testing 187 medical students studying at the medical faculty of Vinnitsa national medical university (test GADS — Goldberg Anxiety and Depression scale). The results indicate the high percentage of persons with anxiety in the group of English-speaking medical students (1 out of 5) and enough high percentage of persons with depression (1 out of 6), while in the group of Ukrainian students these fractions are much smaller (1 out of 20 and 1 out of 10, respectively).